Catalogues’ Analysis of the Independent Publishing Houses in Bogota and Cordoba, Focusing on Children’s and young people’s issued from 2012-2017 (2019)
This paper discusses the partial results that arise from the analysis and revision of the catalogues of the independent publishing houses of Bogotá (Colombia) and Córdoba (Argentina) which publications are aimed at children and young people. This is accompanied, as a context by a problematization that has brought with the influence of public policies on issues in reading promotion synchronized with the flourishing of independent publishers throughout the region in the children’s and youth publishing subsector. Methodologically, with a comparative strategy, the catalogues and the implications of these devices were compared in a five-year observation window. We reviewed variables such as the internal unity of the system, the conversational congruence of texts, the relevance to the context, the recurrent genres, their commitment to the market, aesthetics and poetics, and editorial design. This was complemented with semi-structured interviews with the editors, which allowed for a discussion of what was observed